Effect of Osmotic Dehydration Treatment with Binary/Ternary Osmotic Solutions on the Characteristics of Yellow Peach Blocks - WANG Jingxuan, LÜ Jian, WANG Fengzhao, BI Jinfeng (Shipin Kexue)
In this study, changes in the textural properties, dielectric properties, cell wall polysaccharide content and microstructure of yellow peach blocks were investigated after osmotic dehydration (OD) treatment with binary/ternary osmotic solutions containing sucrose and maltitol. Meanwhile, changes in the soluble sugar content were determined by 1H nuclear magnetic resonance (1H NMR) spectroscopy. Our aim was to clarify the synergistic effect of maltitol and sucrose on improving the properties of yellow peach blocks during OD treatment. Compared to the control group, The hardness, chewiness and adhesiveness of yellow peach blocks treated with a ternary osmotic solution with a 1:4 ratio of sucrose to maltitol (SM14) were significantly reduced. OD resulted in a significant decrease in the impedance (Z) and effective resistance (Rs) as well as a significant increase in the electrostatic capacity (Cs) of yellow peach blocks, suggesting that OD could affect peach pulp cell properties by acting on cell wall polysaccharides. 1H NMR results showed that OD with ternary osmotic solutions significantly reduced the sucrose content in peach fruit block tissue; for the SM14 group, the signal intensity of sucrose and maltitol were 19 803.9 ± 156.00 and 54 934.9 ± 1 239.11, respectively. Meanwhile, the contents of water-soluble pectin (WSP) and CDTA-soluble pectin (CSP) in the SM14 group were increased to (26.63 ± 1.80) mg/g and (21.59 ± 0.71) mg/g, respectively, while the content of Na2CO3-soluble pectin (NSP) was decreased to (27.24 ± 0.46) mg/g compared to the control group. Microstructure analysis showed that round and relatively intact cells with low degree of collapse and a significant increase in cell wall thickness were observed in the SM14 group, demonstrating sucrose and maltitol synergistically protect peach pulp cells. Therefore, ternary osmotic solutions of sucrose maltitol could effectively ameliorate the quality deterioration of yellow peach blocks caused by binary osmotic solutions, broadening the application of sugar alcohol.